Implementation of a General Web Application Program Interface for Geoinformatics - Jan Pytel (Geoinformatics FCE CTU, 2006)
C++ language was used for creating web applications at the department of Mapping and Cartography for many years. Plenty of projects started to be very large-scale and complicated to maintain. Consequently, the traditional way of adding functionality to a Web Server which previously has been used (CGI programs) started being usefulness. I was looking for some solutions - particularly open source ones. I have tried many languages (solutions) and finally I chose the Java language and started writing servlets. Using the Java language (servlets) has significantly simplified the development of web applications. As a result, developing cycle was cut down. Because of Java JNI (Java Native Interface) it is still possible to use C++ libraries which we are using. The main goal of this article is to share my practical experiences with rewriting typical CGI web application and creating complex geoinformatic web application.